Teaching techniques in removable partial dentures dental students of university of Huancayo - Cueva Buendia , Luis Alberton (2020)
OBJECTIVES: To determine whether the use of teaching techniques, affect the learning of the subject of the removable partial denture in cycle VII students of dentistry at Peruvian Andes University. METHODS: This descriptive research and application level, was conducted in a population of 130 students in the seventh cycle of the Faculty of Dentistry Dental Prosthetics course of UPLA during 2011-2012, the sample was 97 students the same who were selected randomly. First teaching techniques discussed in Dentistry students at Peruvian Andes University, then the removable partial denture also applied to these students, for which a survey was used worked.The instrument used was a questionnaire of 15 closed questions. Data were analyzed both quantitatively and qualitatively. RESULTS: It was demonstrated that 95% of the sample agreed that teaching techniques help meet the removable partial denture. CONCLUSION: It has been determined that the use of teaching techniques, learning favorably affect the course of the removable partial denture in cycle VII students of dentistry at Peruvian Andes University.